Alkynyl gold(I) phosphane complexes: evaluation of structure-activity-relationships for the phosphane ligands, effects on key signaling proteins and preliminary in-vivo studies with a nanoformulated complex - Andermark, Vincent; Göke, Katrin; Kokoschka, Malte; Abu El Maaty, Mohamed A.; Lum, Ching Tung; Zou, Taotao; Sun, Raymond Wai-Yin; Aguiló, Elisabet; Oehninger, Luciano; Rodríguez, Laura; Bunjes, Heike; Wölfl, Stefan; et al. (Journal of inorganic biochemistry, 2016)
Gold alkynyl complexes with phosphane ligands of the type (alkynyl)Au(I)(phosphane) represent a group of bioorganometallics, which has only recently been evaluated biologically in more detail. Structure-activity-relationship studies regarding the residues of the phosphane ligand (P(Ph)3, P(2-furyl)3, P(DAPTA)3, P(PTA)3, P(Et)3, P(Me)3) of complexes with an 4-ethynylanisole alkyne ligand revealed no strong differences concerning cytotoxicity. However, a relevant preference for the heteroatom free alkyl/aryl residues concerning inhibition of the target enzyme thioredoxin reductase was evident. Complex 1 with the triphenylphosphane ligand was selected for further studies, in which clear effects on cell morphology were monitored by time-lapse microscopy. Effects on cellular signaling were determined by ELISA microarrays and showed a significant induction of the phosphorylation of ERK1 (extracellular signal related kinase 1), ERK2 and HSP27 (heat shock protein 27) in HT-29 cells. Application of 1 in-vivo in a mouse xenograft model was found to be challenging due to the low solubility of the complex and required a formulation strategy based on a peanut oil nanoemulsion.